Value of ST- Segment Depression with T-Wave Inversion in Lateral Leads I, aVL, V4-V6 in Diagnosing the Left Main or Left Main Equivalent Coronary Artery Disease - Mallick, Sambhu Kumar; Ali, Mahboob; Chowdhury, Amal Kumar (Cardiovascular Journal, 2017)
Background: Critical stenosis in the proximal part of the left anterior descending, severe 3 vessel disease and left main stem stenosis have all been recognized as clinical conditions complicated by a high incidence of large infarction, pump failure, arrhythmias and sudden death in patients with acute coronary syndrome (ACS). As many effective treatment modes are available currently, early recognition of those circumstances is crucial for appropriate management. Methods: this observational study was carried out at the Department of Cardiology, National Institute of Cardiovascular Disease (NICVD), Dhaka. Patients (30 patients) with NSTEACS having ST-segment depression with T-wave inversion maximally in leads I,avL,V4-V6 were considered as cases (Group I) and those (30 patients) with ST-segment depression without T-wave inversion in lateral leads were controls (Group II). Coronary angiogram (CAG) was done during in-hospital stay. Results: In present study, it was evident that among group I patients, 43.3% had stenotic lesion in left main artery (LM) and 26.67% in LM equivalent coronary artery (LME CA), whereas had no stenotic lesion in LM and 3.33% had LME CA lesion in group II patients. Low cost, widely available ECG criteria is supposed to be useful predictor of left main or left main equivalent coronary artery obstruction (Sensitivity=95%, Specificity= 76%, Positive predictive value= 70.0% and Negative predictive value= 97.0%) and high STsegment changes score (>18 mm (100%) &/or ³10mm (80%) was an additive predictor of LM or LMECA lesion. Conclusion: Maximum ST- segment depression with T-wave inversion in the lateral leads I, aVL, V4-V6 on admission ECG can predict the critical LM or LMECA obstruction in patients with NSTEACS. It can help to provide prompt and appropriate management earlier to reduce the mortality & morbidity. Cardiovasc. j. 2017; 9(2): 135-141